Self-rating on Self-directed Learning: A Cross-Sectional Survey on a Cohort of Medical Undergraduates from Nepal - Atreya, Alok; Nepal, Samata; Acharya, Jenash (Journal of Lumbini Medical College, 2020)
Introduction: As medicine is an ever-changing field, it necessitates medical students to develop independent learning skills for continuous learning process. Self-directed learning (SDL) is a learning strategy where students take the initiative to learn on their own. It is basically an independent study where the students use available resources and learn independently of the subject. Methods: This self-administered questionnaire study assessed five domains of SDL consisting of 60 items. The responses were made on a five-point Likert scale: from 5 = always to 1 = never. The level of self-directed learning was categorized as high, moderate and low if the scoring range was between 221-300, 141-220 or 60-140 respectively. Any student scoring in the range between 221 and 300 was considered an effective self- directed learner. Results: The present study found three out of four the students (74.7%, n=56) were active self-directed learners. However, one out of four students were half-way in becoming self-directed learners. Conclusion: SDL skill is crucial not only for the students but also for the clinicians in a complex learning process for continuous advancement of knowledge in medical profession. The findings of the present study showed that majority of the students were effective self-directed learners. The effectiveness of SDL process can be accomplished if the students are encouraged and motivated during Problem Based Learning (PBL) sessions. Identifying the factors that spark interest amongst the students to learn on their own can be achieved by active feedback sessions.